2012
DOI: 10.1038/ejcn.2012.112
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers and metabolic syndrome among adolescents

Abstract: BACKGROUND/OBJECTIVES:The alarming increase in obesity worldwide is of concern, owing to the associations of obesity with metabolic syndrome (MetS), which has been associated with a proinflammatory state characterized by elevated plasma concentrations of several markers of inflammation. The aim of this study was to assess levels of inflammatory markers and their association with MetS among adolescents. SUBJECTS/METHODS: A random sample of adolescents (n ¼ 362, 143 boys and 219 girls, 12-17 years) was interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 47 publications
2
36
0
1
Order By: Relevance
“…It has been established that insulin levels and the frequency of insulin resistance increase as puberty progresses (29). The effects of sex steroids are also reflected in leptin levels, which increase during puberty as well (26). Although studies enrolling prepubertal children exclusively are rare, it is known that some risk factors for cardiovascular disease are already present at this age, as shown in our investigation.…”
Section: Discussionmentioning
confidence: 70%
“…It has been established that insulin levels and the frequency of insulin resistance increase as puberty progresses (29). The effects of sex steroids are also reflected in leptin levels, which increase during puberty as well (26). Although studies enrolling prepubertal children exclusively are rare, it is known that some risk factors for cardiovascular disease are already present at this age, as shown in our investigation.…”
Section: Discussionmentioning
confidence: 70%
“…14 In our sample, no association of TNF-a, IL-6 and PAI-1 with adiposity indices was observed in girls. 39 In the literature, there is no consensus regarding TNF-a concentration; some studies have found high concentrations while others have not. 38 A previous study that assessed the association between IL-6 and TNF-a, adiposity, fat cell size and insulin sensitivity in a group of overweight and obese prepubertal children found that adipocity size, more than BMI and fat mass, was significantly associated with both inflammatory markers.…”
Section: Discussionmentioning
confidence: 98%
“…However, their clinical advantages as markers of MS have not been assessed, so that their use as screening tools for MS is not justified [17,76,77,78,79,80]. …”
Section: Markers Of Co-morbiditiesmentioning
confidence: 99%
“…Several circulating markers, such as uric acid, alanine aminotransferase, adiponectin, leptin, resistin, retinol binding protein 4, plasminogen activator inhibitor-1 and other inflammatory markers, as well as novel adiposity markers, such as epicardial fat, have been associated with MS, fueling the research on the pathogenesis, long-term prediction and treatment of cardio-metabolic disease [17,76,77,78,79,80]. However, their clinical advantages as markers of MS have not been assessed, so that their use as screening tools for MS is not justified [17,76,77,78,79,80].…”
Section: Markers Of Co-morbiditiesmentioning
confidence: 99%